Keywords for children's literature - Nel, Philip 1969-; Paul, Lissa 1953-; Christensen, Nina 1968- (New York University Press, 2021)
"This title is a second edition of the "Keywords for Children's Literature." This work provides a list of essential terms for the study of children's literature with a discussion of each term"--
Keywords: Kinderliteratur; Englisch; Children's literature / History and criticism / Terminology; Children's literature; Terminology; Criticism, interpretation, etc; Wörterbuch